ChemInform Abstract: Efficient Synthesis of Pharmaceutically Important Fluorinated Benzo[b]furans. Issue 49 (9th December 2014) - Jain, Meenakshi; Tiwari, Anjali
Abstract All new fluorinated benzo[b]furans (II) (6 examples) show promising antibacterial and antifungal activities against S.